Komentar untuk artikel Savitri et al.: Implementasi algoritma genetika dalam mengestimasi kepadatan populasi jackrabbit dan coyote - Najib, Mohamad Khoirun; Nurdiati, Sri (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This article is a commentary on research conducted by Savitri et al which was published in Jambura Journal of Biomathematics volume 3 number 1 in 2022. It was found that there was an error in the MAPE calculation for the approximation of population density of coyote. The MAPE obtained for coyotes was 66.05% so there was a significant difference from what had been given before. With these results, there is an opportunity to estimate parameters with better accuracy.